Uptake of and Resistance to the Antibiotic Berberine by Individual Dormant, Germinating and Outgrowing Bacillus Spores as Monitored by Laser Tweezers Raman Spectroscopy - Wang, Shiwei; Yu, Jing; Suvira, Milomir; Setlow, Peter; Li, Yong-qing (PloS one, 2015)
Berberine, an alkaloid originally extracted from the plant Coptis chinensis and other herb plants, has been used as a pharmacological substance for many years. The therapeutic effect of berberine has been attributed to its interaction with nucleic acids and blocking cell division. However, levels of berberine entering individual microbial cells minimal for growth inhibition and its effects on bacterial spores have not been determined. In this work the kinetics and levels of berberine accumulation by individual dormant and germinated spores were measured by laser tweezers Raman spectroscopy and differential interference and fluorescence microscopy, and effects of berberine on spore germination and outgrowth and spore and growing cell viability were determined. The major conclusions from this work are that: (1) colony formation from B. subtilis spores was blocked ~ 99% by 25 μg/mL berberine plus 20 μg/mL INF55 (a multidrug resistance pump inhibitor); (2) 200 μg/mL berberine had no effect on B. subtilis spore germination with L-valine, but spore outgrowth was completely blocked; (3) berberine levels accumulated in single spores germinating with ≥ 25 μg/mL berberine were > 10 mg/mL; (4) fluorescence microscopy showed that germinated spores accumulated high-levels of berberine primarily in the spore core, while dormant spores accumulated very low berberine levels primarily in spore coats; and (5) during germination, uptake of berberine began at the time of commitment (T1) and reached a maximum after the completion of CaDPA release (Trelease) and spore cortex lysis (Tlysis).